Umbilicoplasty by vertical incision: description of the technique and assessment of satisfaction - Diogo Borges Pedroso; Daniel Augusto dos Santos Soares; Marcela Caetano Cammarota; Leonardo Martins Costa Daher; Milena Carvalho Almeida Galdino; Gabriel Campelo dos Santos; Leonardo David Pires Barcelos; José Carlos Daher (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: The abdomen is an important aesthetic functional segment in the characterization of the body contour. In abdominoplasty, the placement and shape of the umbilical scar are important for a satisfactory result. This study aimed to describe the technique of vertical omphaloplasty and to present the results obtained. METHODS: Retrospective longitudinal descriptive study composed of patients who underwent vertical omphaloplasty during classic abdominoplasty between 2014 and 2017. The technique consists of a vertical transcutaneous incision without removal of the skin spindle and with minimal degreasing of the wall around the umbilicus, followed by the transfixing a point in the lateral portion of the umbilical pedicle, allowing its invagination and fixation close to the aponeurosis of the rectus abdominis. RESULTS: In the 128 patients evaluated, the patients' age ranged from 25 to 62 years, with a mean of 32 years. The mean time of surgery was 2 h and 33 min. No surgical complications occurred, such as hematoma or abdominal flap necrosis. Two cases of dehiscence, four cases of hypertrophic scar, two cases of stenosis, and one case of umbilical necrosis were observed. In outpatient follow-up, 92.2% of the patients were very satisfied with the final result. The technical analysis presented an 88% degree of satisfaction. CONCLUSION: The technique described presents satisfactory results, reduces the possibility of the appearance of a cicatricial ring, and allows minimizing one of the stigmas of abdominoplasty, which is a very visible umbilical scar.